Comparative Effectiveness of Percutaneous Needle Aponeurotomy and Limited Fasciectomy for Dupuytren's Contracture: A Multicenter Observational Study. Issue 4 (October 2016) - Zhou, Chao; Selles, Ruud W.; Slijper, Harm P.; Feitz, Reinier; van Kooij, Yara; Moojen, Thybout M.; Hovius, Steven E. R.
Abstract : Background: Percutaneous needle aponeurotomy is a less invasive surgical alternative to limited fasciectomy for Dupuytren's contracture, but appeared less efficacious in a previous randomized clinical trial. This study compared the effectiveness of both techniques in contemporary clinical practice. Methods: The authors evaluated prospectively gathered data from all patients who were treated with percutaneous needle aponeurotomy or limited fasciectomy between 2011 and 2014 at six hand surgery practice sites in The Netherlands. The degree of total active extension deficit, Michigan Hand Outcomes Questionnaire subscores, and complications evaluated at 6 to 12 weeks after treatment were compared after propensity score–based inverse-probability weighting to account for the differences in baseline characteristics between the treatment groups. Results: After inverse-probability weighting, 78 percutaneous needle aponeurotomy patients and 103 limited fasciectomy patients remained with similar characteristics (88 percent Tubiana grade I or II). The degree of total residual extension deficit at follow-up was similar between the weighted groups (percutaneous needle aponeurotomy, 21 degrees; limited fasciectomy, 18 degrees; p = 0.330). Furthermore, percutaneous needle aponeurotomy was associated with a lower mild complication rate (percutaneous needle aponeurotomy, 5.2 percent; limited fasciectomy, 24.3 percent; p < 0.001) and larger increases in the subdomain scores of satisfaction ( p < 0.001), work performance ( p < 0.001), activities of daily living ( p = 0.009), and overall hand function ( p = 0.001). Conclusions: This multicenter observational study found that, among patients with mildly to moderately affected digits, percutaneous needle aponeurotomy reduced contractures as effectively as limited fasciectomy does in clinical practice. Furthermore, percutaneous needle aponeurotomy provided a more rapid functional recovery and had a lower rate of mild complications. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Coding Perspective for this Article is on Page 845.